Efficacy and Safety of Aprocitentan in the Treatment of Hypertension: A Meta-Analysis of Evidence from Randomized Controlled Trials - Li Zheng; Ming Liu; Xiaotong Gu; Yatong Zhang; Yan Wang (Reviews in Cardiovascular Medicine)
Background: Hypertension is one of the most prevalent disorders encountered in medical practice, yet effective pharmacotherapy options for resistant hypertension are limited. In this meta-analysis, we aimed to evaluate the efficacy and safety of aprocitentan in treating hypertension. Methods: We searched PubMed, Embase, ClinicalTrials.gov, and the Cochrane Library databases from inception to June 3, 2024, for randomized controlled trials (RCTs) that compared the efficacy and safety between aprocitentan and placebo in treating hypertension. According to the dosage of aprocitentan, the study was divided into a low-dose group (10–12.5 mg), medium-dose group (25 mg), and high-dose group (50 mg). Results: This meta-analysis included five RCTs, which incorporated 1224 patients, and displayed that aprocitentan can reduce the mean sitting systolic blood pressure (msSBP) [(low dose subgroup: mean difference (MD): –3.85 mmHg; 95% confidence interval (CI): –7.47 to –0.23; p = 0.040; medium dose group: MD: –5.56 mmHg; 95% CI: –10.69 to –0.44; p = 0.030)], mean sitting diastolic blood pressure (msDBP) (low dose subgroup: MD: –3.95 mmHg; 95% CI: –4.06 to –3.85; p < 0.001; medium dose group: MD: –4.75 mmHg; 95% CI: –5.91 to –3.60; p < 0.001), 24-hour ambulatory systolic blood pressure (maSBP) (low dose group: MD: –4.18 mmHg; 95% CI: –4.32 to –4.04; p < 0.001; medium dose group: MD: –5.89 mmHg; 95% CI: –6.03 to –5.75; p < 0.001), and 24-hour ambulatory diastolic blood pressure (maDBP) (low dose group: MD: –4.33 mmHg; 95% CI: –4.42 to –4.24; p < 0.001; medium dose group: MD: –5.82 mmHg; 95% CI: –5.91 to –5.73; p < 0.001). In the high-dose group, there was no difference between the aprocitentan and placebo groups in the msSBP (MD: –4.83 mmHg; 95% CI: –11.44 to 1.79; p = 0.150). Meanwhile, the safety profile of aprocitentan was good, and no significant differences in the frequency of adverse events (AEs) and serious adverse events (SAEs) were observed compared to the placebo. Conclusions: Aprocitentan significantly reduces blood pressure and has a good safety profile. However, it is worth noting that high doses of aprocitentan (50 mg) did not yield better blood pressure-lowering effects.